Організаційно-правові обриси "Східного партнерства" - Вишняков, Олександр Костянтинович; Вишняков, Александр Константинович; Vishnjakov, Aleksandr (My University, 2009)
The n e w e s t EU initiative of «Eastern Partnership» has become a significant move in development of the all-round dialogue between Ukraine and the EU, including legal issues. The EP is a f u n d a m e n t a l l y n e w form in m u l t i l a t e r a l c o o p e r a t i o n with t h e EU with participation of U k r a i n e , as it said openly about t h e i n t e g r a t i o n direction of s u c h coooperation. It has more precise objectives — «political association and economic integration between the EU and interested partner-countries». Formulation of the A g r e e m e n t on the Free Trade Area within the EP framework as a deep and comprehensive, p r e s u m i n g the WTO legal s t a n d a r d s , obviously, stipulates additional e l e m e n t s of EU «four freedoms». The EP has a precise multilateral organizational-legal basis: it concerns the s y s t e m of c o m m o n decision-making. The principles, on which t h e EP is based, — i n t e r n a t i o n a l law and fundamental values, including democracy, rule of law and respect for h u m a n rights, as well as m a r k e t economy, s u s t a i n a b l e d e v e l o p m e n t and good g o v e r n a n c e . It offers n e w challenges for d e v e l o p m e n t of the economic dialogue b e t w e e n t h e i n t e g r a t e d and non-i n t e g r a t e d E u r o p e as well as d e v e l o p m e n t of n e w legal relations, p r o c e s s i n g of n e w c o m m o n legal values on this basis. Thus, gradual convergence of Ukraine with the EU in the legal area, would contribute to further progress in EU — Ukraine relations.
Вишняков О. К. Організаційно-правові обриси "Східного партнерства" / О. К. Вишняков // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 223-232.
Keywords: інтеграція; конвергенція; діалог; правова система; правові принципи; правові цінності; політична асоціація; економічна інтеграція; зона вільної торгівлі; интеграция; конвергенция; диалог; правовая система; правовые принципы; правовые ценности; политическая ассоциация; экономическая интеграция; зона свободной торговли; integration; convergence; dyalog; legal system; legal principles; policy association; economic integration; free trade zone